2020
DOI: 10.3390/ijms21249676
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Metabolism in Breast Cancer Microenvironment: Contribution Focused on Associated Adipose Tissue and Obesity

Abstract: Metabolic reprogramming that favors high glycolytic flux with lactate production in normoxia is among cancer hallmarks. Lactate is an essential oncometabolite regulating cellular redox homeostasis, energy substrate partitioning, and intracellular signaling. Moreover, malignant phenotype’s chief characteristics are dependent on the interaction between cancer cells and their microenvironment. In breast cancer, mammary adipocytes represent an essential cellular component of the tumor milieu. We analyzed lactate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…A recent in vitro study on ovarian cancer indicated a possible relationship between glycogen metabolism and cancer proliferation and metastasis, partly through stimulation of glycolysis and lactate production [ 66 ]. We recently showed that breast cancer tissues in normal-weight women have significantly higher tissue lactate concentration than those in obese women, unrelated to LDH activity and protein expression [ 25 ], which could be related to the more pronounced glycogen deposition as shown in this study. In contrast, breast cancer tissues of overweight/obese women showed higher PFK-1 and GAPDH protein expression compared to breast cancer tissues of normal-weight women.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A recent in vitro study on ovarian cancer indicated a possible relationship between glycogen metabolism and cancer proliferation and metastasis, partly through stimulation of glycolysis and lactate production [ 66 ]. We recently showed that breast cancer tissues in normal-weight women have significantly higher tissue lactate concentration than those in obese women, unrelated to LDH activity and protein expression [ 25 ], which could be related to the more pronounced glycogen deposition as shown in this study. In contrast, breast cancer tissues of overweight/obese women showed higher PFK-1 and GAPDH protein expression compared to breast cancer tissues of normal-weight women.…”
Section: Discussionmentioning
confidence: 78%
“…Currently, cancer-adipose tissue cross-talk is studied as an important example of cancer-stroma metabolic cooperation [ 22 , 23 ]. Adipocytes can engage in intracellular trafficking of many metabolites, including fatty acids, glycerol, ketone bodies, lactate, as well as whole exosomes with cancer cells [ 24 , 25 ]. However, little is known about the mechanisms of adipose tissue metabolic reprogramming that enables such metabolic coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible target in adipocyte-tumor cell cross-talk is lactate dehydrogenase (LDH), a key metabolic enzyme in the conversion between pyruvate and lactate that regulates nutrient exchange between tumor and stromal cells in the tumor microenvironment, supporting tumor progression. Higher lactate production, concomitant with higher LDHA (converting pyruvate to lactate) and lower LDHB (converting lactate to pyruvate) expression in malignant BC compared with benign disease, has been observed, mainly in normal-weight patients [ 6 ]. Adipose tissue that is adjacent to tumor tissue increases LDH activity—primarily LDHB—facilitating lactate oxidation in adipocytes in stromal–epithelial metabolic coupling [ 6 ].…”
mentioning
confidence: 99%
“…Higher lactate production, concomitant with higher LDHA (converting pyruvate to lactate) and lower LDHB (converting lactate to pyruvate) expression in malignant BC compared with benign disease, has been observed, mainly in normal-weight patients [ 6 ]. Adipose tissue that is adjacent to tumor tissue increases LDH activity—primarily LDHB—facilitating lactate oxidation in adipocytes in stromal–epithelial metabolic coupling [ 6 ].…”
mentioning
confidence: 99%